THE ANTICOAGULATION OF CALF THROMBOSIS (ACT) PROJECT: RESULTS FROM THE RANDOMISED CONTROLLED EXTERNAL PILOT TRIAL. Issue 10 (7th September 2013) - Horner, D; Hogg, K; Body, R; Nash, M J; Mackway-Jones, K
Abstract : Objectives & Background: There is currently little evidence defining the clinical importance of detecting and treating isolated distal deep vein thrombosis (IDDVT). Contemporary international guidelines vary regarding diagnostic and therapeutic advice. The potential benefits of anticoagulation remain poorly defined. We sought to evaluate the feasibility of a randomised controlled trial within a modern emergency department cohort. Methods: A pragmatic, open label, external pilot randomised controlled trial conducted from January 2011 to April 2012. Consecutive ambulatory symptomatic IDDVT patients were approached for inclusion. Participants were randomised to receive either conservative management (control) or phased therapeutic anticoagulation (intervention). All patients underwent assessor blinded color duplex imaging after 7 and 21 days, and clinical follow up at three months. Principal feasibility outcomes were recruitment rate and attrition. The primary clinical outcome was a composite of proximal propagation, pulmonary embolism, death attributable to venous thromboembolic disease or major bleeding. Analysis was by intention to treat. Results: Acute IDDVT was detected in 93 cases. 79 were subsequently deemed eligible and 70 (88.6% of those eligible) recruited. 59/70 (84.3%, 95% CI 74.0–91.0%) patients completed the full protocol. All patients but 1 were followed up by direct contact after 90 days. Allocation crossover occurred in 15 (21.4%) cases. All predefined feasibility outcomes were achieved. The primary clinical outcome occurred in 4/35 (11.4%) controls and 0/35 in the intervention group (Absolute Risk Reduction [ARR] 11.4%, 95% Confidence Interval [CI] −1.5 to 26.7, p=0.11, number needed to treat [NNT] of 9). There were no cases of major bleeding in either group. Propagation to any site occurred in 11/35 (31.4%) of conservatively treated patients compared with 2/35 (5.7%) of those randomized to anticoagulation (ARR 25.7%, 95% CI 5.9 to 44.3%, P=0.001, NNT 4). Minor bleeding occurred in 3/35 (8.6%) controls and 7/35 (20.0%) anticoagulated patients (p=0.31). Conclusion: We have established feasibility for a definitive trial on the value of therapeutic anticoagulation for IDDVT. Our pilot study currently provides the largest prospective randomised clinical dataset on this topic and demonstrates a non-significant trend towards reduction in complications with anticoagulation.